At risk: betting-related match-fixing in Brazilian football - Marchetti, Felippe (Crime, law and social change, 2021)
Brazilian football is strongly affected by betting-related match-fixing, as indicated by numerous incidents over the past years. However, little remains known about the underlying factors that contribute to the country’s vulnerability towards this form of corruption in sport. Hence, this study applies the lens of sociological institutionalism to examine some of the risk factors that make Brazilian football susceptible to betting-related match-fixing. An exploratory multi-methods study design was applied, including the analysis of policy and judicial documents and semi-structured interviews with key anti-match-fixing actors (n = 7) and sport actors (n = 15) in Brazilian football. Content analysis highlights the influence of deeply rooted characteristics and institutionalized norms in Brazilian football, such as a low prioritization of counteracting match-fixing, many unmonitored matches, poorly governed sport organizations, and poor working conditions for players and referees. In the end, this study helps to gain a better understanding of betting-related match-fixing in Latin America, while informing criminal policy to address and prevent this issue.